MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN MELALUI METODE BERMAIN PERAN - Tuti Farida; Laily Rosidah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2018)
The ability to speak can be interpreted as articulation sounds or say words to express, express, convey the thoughts, ideas and feelings of listeners receive information through a series of tones, pressures and word placement. The purpose of this research is to know the process of applying the macro role playing method and the improvement of speech ability of the children in group B through the macro role playing method in Darul Irfan Pakupatan, Serang-Banten kindergarten. The benefits of this research can optimize the development of speaking skills of children aged 5-6 years, facilitate teachers in teaching the ability to speak in a way that is fun and interesting for children and increase knowledge insight in improving children’s speaking ability. The method used in this research is the method of action research (PT), in this study consists of two cycles. In the first cycle of 8 actions and cycle II as much as 4 times the action, with the success of the action reached 60%. The subjects of this study were children aged 5-6 years with a total of 12 children consisting of 7 girls and 5 boys. Based on the result of the research, it can be concluded that the ability to speak of children aged 5-6 years through role-playing method with the results of this study is known that the pre-action condition is 26%, then in cycle I increases to 40%, while in cycle II, significantly reaching 84% and experiencing success on already targeted indicators. Based on the results of data that have been obtained can be concluded that with the application of the method of playing the role of macro can improve the speaking ability of children aged 5-6 years in kindergarten Darul Irfan Pakupatan, Serang-Banten.